Should influenza vaccination be mandatory for healthcare workers?. Issue 5 (September 2018) - Lukich, Nikolija; Kekewich, Michael; Roth, Virginia
Each year, many healthcare organizations deal with low influenza immunization rates among staff. Mandatory influenza vaccination programs may be considered in order to address this issue. These types of programs have caused controversy in the past, as staff has argued that they infringe upon their liberties and right to autonomy. However, if viewed from a public health perspective, mandatory vaccination programs are beneficial for both employees and patients and can be justified. When individuals make the decision to work in the medical field, it is assumed that their values align with those of the organization for which they work. This overrides their right to autonomy, since they are expected to put the safety of their patients ahead of their own personal interests. Although some may argue that receiving a flu shot is unsafe, evidence has demonstrated the opposite, and the minimal discomfort that may result from a vaccine is not enough to negate the responsibilities that healthcare workers have toward the patients they serve.